2011
DOI: 10.5047/eps.2011.05.015
|View full text |Cite
|
Sign up to set email alerts
|

A rupture model of the 2011 off the Pacific coast of Tohoku Earthquake

Abstract: The 11 March 2011 Tohoku Earthquake ruptured the interplate boundary off-shore of east Japan, with fault displacements of up to 40 m and a rupture duration of 150-160 s. W-phase inversion indicates a moment of 3.9 × 10 22 N m (M w 9.0) and a centroid time of 71 s. We invert teleseismic P waves and broadband Rayleigh wave observations with high-rate GPS recordings from Japan to characterize the rupture. The resulting rupture model begins with a steady increase of moment rate for the first 80 s, and a rupture sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
181
1
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(200 citation statements)
references
References 19 publications
16
181
1
2
Order By: Relevance
“…22 N m (J-Mod) to 4.1×10 22 N m (Pmod), compatible with long-period determinations of seismic moment (∼3.9×10 22 N m; Ammon et al, 2011); and have maximum slips of about 40 m, with average slip of about 15 m over the regions of the fault models where slip is well-resolved. Even larger slips at very shallow depth are proposed by other inversions (e.g., Lay et al, 2011c), and the calculations based on these models can be viewed as a conservative estimate for stress changes.…”
Section: The 11 March 2011 Rupturesupporting
confidence: 77%
See 1 more Smart Citation
“…22 N m (J-Mod) to 4.1×10 22 N m (Pmod), compatible with long-period determinations of seismic moment (∼3.9×10 22 N m; Ammon et al, 2011); and have maximum slips of about 40 m, with average slip of about 15 m over the regions of the fault models where slip is well-resolved. Even larger slips at very shallow depth are proposed by other inversions (e.g., Lay et al, 2011c), and the calculations based on these models can be viewed as a conservative estimate for stress changes.…”
Section: The 11 March 2011 Rupturesupporting
confidence: 77%
“…2. Maps of slip distributions for two finite-faulting models derived from teleseimic P-waves (left) and joint inversion of P waves, Rayleigh waves and continuous GPS observations (right, adapted from Ammon et al, 2011). The P wave inversion model has variable rake of the subfaults, indicated by the small vectors; the joint inversion has uniform rake of 85 • .…”
Section: The 11 March 2011 Rupturementioning
confidence: 99%
“…Many source inversion and geodetic modeling results have shown that the primary seismic moment contributions of the 2011 Tohoku mainshock were from the up-dip portion, possibly extending to the trench (Ammon et al, 2011;Iinuma et al, 2011;Lay et al, 2011b;Miyazaki et al, 2011) and that the source area was relatively strongly coupled (Mazzotti et al, 2000;Hashimoto et al, 2009;Loveless and Meade, 2010;Uchida and Matsuzawa, 2011). We thus propose a first scenario to explain the occurrence of the 2011 Tohoku-Oki, and the 2003 Tokachi-Oki, earthquakes.…”
Section: Conceptual Mode Of Megathrust Eventmentioning
confidence: 76%
“…This inference is supported by comparison of the high-rate GPS records with seismic records and synthetic seismograms. (Ammon et al, 2011;Simons et al, 2011;Fig. 1).…”
Section: Introductionmentioning
confidence: 99%